Dietary Phytochemicals: Natural Swords Combating Inflammation and Oxidation-Mediated Degenerative Diseases. (19th September 2016) - Islam, Md. Asiful; Alam, Fahmida; Solayman, Md.; Khalil, Md. Ibrahim; Kamal, Mohammad Amjad; Gan, Siew Hua
Abstract : Cumulatively, degenerative disease is one of the most fatal groups of diseases, and it contributes to the mortality and poor quality of life in the world while increasing the economic burden of the sufferers. Oxidative stress and inflammation are the major pathogenic causes of degenerative diseases such as rheumatoid arthritis (RA), diabetes mellitus (DM), and cardiovascular disease (CVD). Although a number of synthetic medications are used to treat these diseases, none of the current regimens are completely safe. Phytochemicals (polyphenols, carotenoids, anthocyanins, alkaloids, glycosides, saponins, and terpenes) from natural products such as dietary fruits, vegetables, and spices are potential sources of alternative medications to attenuate the oxidative stress and inflammation associated with degenerative diseases. Based on in vitro, in vivo, and clinical trials, some of these active compounds have shown good promise for development into novel agents for treating RA, DM, and CVD by targeting oxidative stress and inflammation. In this review, phytochemicals from natural products with the potential of ameliorating degenerative disease involving the bone, metabolism, and the heart are described.